1994
DOI: 10.1093/mutage/9.4.383
|View full text |Cite
|
Sign up to set email alerts
|

Antigenotoxicity of coffee in the Drosophila assay for somatic mutation and recombination

Abstract: The somatic mutation and recombination test (SMART) in Drosophila melanogaster was carried out to investigate whether or not coffee can modulate the genotoxicity of the well-established mutagenic/carcinogenic chemicals cyclophosphamide (CPH), diethylnitrosamine (DEN), mitomycin C (MMC), procarbazine (PRO) and urethane (URE). For this purpose, 3-day-old larvae, trans-heterozygous for the wing hair markers mwh (multiple wing hairs) and flr3 (flare3), were raised on instant medium containing either the genotoxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 0 publications
1
74
0
4
Order By: Relevance
“…It has been demonstrated by the wing spot test that the co-administration of coffee is effective in significantly reducing the frequencies of single and twin spots induced by cyclophosphamide, Ascorbic acid modulation of doxorubicin genotoxicity 451 diethylnitrosamine, mitomicyn C, procarbazine and urethane (Abraham, 1994) and that turmeric inhibited the genotoxic effect of urethane (El Hanss et al, 1999). Furthermore, sodium selenite has been shown to be antigenotoxic in combination with potassium dichromate (Rizki et al, 2001) and AA modulated the genotoxic action of several mutagens (Kaya et al, 2002), showing the suitability of this test system for mimicking the normal intake of substances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated by the wing spot test that the co-administration of coffee is effective in significantly reducing the frequencies of single and twin spots induced by cyclophosphamide, Ascorbic acid modulation of doxorubicin genotoxicity 451 diethylnitrosamine, mitomicyn C, procarbazine and urethane (Abraham, 1994) and that turmeric inhibited the genotoxic effect of urethane (El Hanss et al, 1999). Furthermore, sodium selenite has been shown to be antigenotoxic in combination with potassium dichromate (Rizki et al, 2001) and AA modulated the genotoxic action of several mutagens (Kaya et al, 2002), showing the suitability of this test system for mimicking the normal intake of substances.…”
Section: Discussionmentioning
confidence: 99%
“…c Frequency of clone formation: clones/flies/48,800 cells (without size correction). d Calculated as [DXR alone -DXR + AA) / DXR alone] X 100, according to Abraham (1994). e Including rare flr 3 single spots.…”
Section: Discussionmentioning
confidence: 99%
“…The frequencies of clone induction per 10 5 cells were used to determine the recombinogenic activity based on the following parameters: mutation frequency (F M ) = frequency of clones in BH flies/frequency of clones in MH flies, recombination frequency (F R ) = 1-F M , frequency of the total number of spots (F T ) = total number of spots in MH flies (considering mwh and flr 3 spots)/number of flies, frequency of mutation = F T x F M and frequency of recombination = F T x F R (Santos et al, 1999;Sinigaglia et al, 2006). Based on the control-corrected spot frequencies per 10 5 cells the percentage of inhibition by P. ginseng was calculated as (DOX alone -P. ginseng plus DOX/DOX alone) x 100 (Abraham, 1994). Tables 1 and 2 show the wing SMART results for the chronic treatment of larvae with P. ginseng alone (2.5, 5.0 or 10.0 mg/mL) or in combination with DOX (0.125 mg/mL) using flies from ST and HB crosses, respectively.…”
Section: Data Evaluation and Statistical Analysismentioning
confidence: 99%
“…These values were then employed to estimate the contribution of recombination and mutation to the incidence of total mutant spots per fly in trans-heterozygous flies (Andrade et al, 2004). The inhibition percentages (IP) were calculated using the total number of spots per wing with the following formula (Abraham, 1994 …”
Section: Discussionmentioning
confidence: 99%
“…Based on the clone induction frequency per 10 5 cells, we compared the number of observed spots in MH and BH flies and quantified the relative contribution (%) of mutation and recombination to the total number of observed spots (Frei et al, 1992;Abraham, 1994). Comparing the clone induction frequency obtained with DXR alone between geno types, we observed that 15.14% of the mutant clones produced in ST flies were a result of mutation and 84.86% resulted from recombination.…”
Section: Smartmentioning
confidence: 99%